A Clinical Audit on the Compliance of Ultrasound Users to the Standard Operating Procedure of Ultrasonography in a Private Radiologic Academy - Y Yuliawati; P Dioso (ASEAN Journal on Science and Technology for Development, 2016)
This clinical audit identified the compliance rate of ultrasound users to the standard operating procedures (SOP); and identified the factors that led to a compliance rate of ultrasound human users. The review was conducted for six days in a private radiologic academy in Indonesia. Only 23 subjects selected randomly were audited. Of the 23 participants, there were 11 males and 12 females. Of the 11 males, seven were compliant, and three were non-compliant. Of the 12 females, eight were compliant, and four were non-compliant. The factors that affect the compliance to the SOP were based on the skills of the participants. Another factor identified was the way the standard operating procedure communicated to the human users on how to perform the ultrasound. Further training was therefore planned.